Bio-inspired carbon nitride mesoporous spheres for artificial photosynthesis: Photocatalytic cofactor regeneration for sustainable enzymatic synthesis - Huang, J.; Antonietti, M.; Liu, Jian (R S C Publications, 2014)
Inspired by the photosynthetic thylakoid membrane of chloroplasts, we present here the rational design of mesoporous structured colloids made up of graphitic carbon nitride nanosheets and demonstrate their application in photocatalytic NADH regeneration for sustainable enzymatic synthesis. This journal is © the Partner Organisations 2014.